Mapping the mortality-to-incidence ratios of Alzheimer’s Disease and Related Dementias (ADRDs): Evidence from the South Carolina Alzheimer’s disease registry - Eric Mishio Bawa; Daniel A. Amoatika; Margaret C. Miller; Bankole A. Olatosi; Lorie Donelle; Sue E. Levkoff; James W. Hardin; Xiaoming Li; Leonardo Bonilha; Daniela B. Friedman; Swann Arp Adams (PLoS ONE, 2025)
Introduction Mortality-to-incidence ratios (MIRs) are useful in assessing disease burdens and illustrating disparities. Unlike cancer, MIRs have not been applied to ADRDs. Therefore, we estimated and mapped the MIRs for ADRDs to show disparities in South Carolina. Methods Using data from the South Carolina Alzheimer’s Disease Registry (2017−2021), ADRD MIRs were calculated by demographic and geospatial characteristics. To account for the influence of the COVID-19 pandemic, data from 2015 to 2019 were also examined. MIRs were calculated as age-adjusted mortality rates divided by age-adjusted incidence rates. Results Overall, Black people and rural individuals consistently experienced higher MIRs, with the COVID-19 pandemic increasing this disparity gap. MIRs greater than 1.00 were only observed among Black people. The MIR for 31 out of 46 counties exceeded the state average. Discussion Estimating and mapping ADRDs has aided in identifying specific areas with the greatest burden of ADRD in South Carolina for targeting interventions.